Accrual-based and real earnings management before and after IFRS adoption: The case of Greece. Issue 1 (8th February 2016) - Ferentinou, Aikaterini C.; Anagnostopoulou, Seraina C.
Abstract : Purpose: – The purpose of this study is to examine the use of accrual-based vs real earnings management (EM) by Greek firms, before and after the mandatory adoption of International Financial Reporting Standards (IFRS). The research is motivated by the fact that past studies have indicated the existence of significant levels of EM for Greece in particular before IFRS. Design/methodology/approach: – Accrual-based earnings management (AEM) is examined by assessing performance-adjusted discretionary accruals, while real earnings management (REM) is defined in terms of abnormal levels of production costs, discretionary expenses, and cash flows from operations, for a three-year period before and after the adoption of IFRS in 2005. Findings: – The authors find evidence on a statistically significant shift from AEM to REM after the adoption of IFRS, indicating the replacement of one form of EM with the other. Research limitations/implications: – The validity of the results depends on the ability of the empirical models used to efficiently capture the existence of AEM and REM. Practical implications: – IFRS adoption aims to improve accounting quality, especially in countries with high need for such an improvement; however, the tendency to substitute one form of EM with another highlights unintended consequences of IFRS adoption, which do not improve the informational content of financial statements if EM continues under different forms. Originality/value: – Under the expectation that IFRS adoption should lead to improvements in accounting quality, this study examines whether IFRS actually led to a reduction of EM practices for a country with exceptionally high levels of EM before IFRS, by accounting for all possible forms of EM.